2021
DOI: 10.21037/jhmhp-20-93
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Gini coefficient of healthcare resources in China from 1998 to 2016

Abstract: Background: Healthcare disparities in China are attracting attention not only in the country but also worldwide. However, few studies have evaluated the changes in equality of healthcare resource distribution among provinces in China. This study was conducted to provide healthcare resource allocation advice to government medical management institutions. We aimed to (I) analyze changes in healthcare disparities in China from 1998 to 2016 through data visualization and (II) determine what factors are related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Overall, the allocation of health workforce in THCs is relatively fair and the Gini coefficient for both doctors density and nurses density have decreased. This is consistent with previous studies [ 8 , 63 , 64 ]. The reason for this is that some low-level areas, especially those that previously experienced a shortage of licensed doctors and registered nurses, have increased their allocation level, while areas with higher levels of allocation kept their number of health technicians stable, narrowing the gap between regions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Overall, the allocation of health workforce in THCs is relatively fair and the Gini coefficient for both doctors density and nurses density have decreased. This is consistent with previous studies [ 8 , 63 , 64 ]. The reason for this is that some low-level areas, especially those that previously experienced a shortage of licensed doctors and registered nurses, have increased their allocation level, while areas with higher levels of allocation kept their number of health technicians stable, narrowing the gap between regions.…”
Section: Discussionsupporting
confidence: 94%
“…Despite these notable advancements, China's healthcare system continues to grapple with significant challenges, one of which pertains to the uneven allocation of healthcare resources [ [8] , [9] , [10] , [11] ]. Even within the same city, like Shanghai, which represents the highest level of urbanization in China, there still existed regional difference [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Chinese study, for example, used data from the Chinese Statistical Yearbook (1999-2017) from 2008 to 2016, the Gini coefficients for healthcare institutions fluctuated between 0.150 and 0.200, fell by 0.048 (39.5%) and 0.058 (40.9%), respectively. At the same time that the number of nurses is growing at the fastest pace (109.0%), the distribution of nurses is also of the utmost importance [ 10 ]. In another study conducted in 18 states of Sudan using state-level data on health resources and health outcomes from the Sudan Health Statistical Report of 2016, the Gini coefficient values vary from 0.32 for hospitals and 0.36 for healthcare centers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on published studies, China had an imbalance distribution of health services among other areas and had gaps between urban and suburban areas [ 12 ]. A Chinese study showed that inequalities existed between urban and suburban areas due to an imbalance of economic levels and differences in land size and population [ 13 , 14 ]. Many studies have focused on equality research and used the Gini or Theil Indexes, popular methods in this field [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%